DISKURSUS KRITIK MATAN; Tashih Isnad terhadap Kontroversi Riwayat Rasulullah SAW Menyalatkan Ibn Ubay - Muhamad Ridwan Nurrohman (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2019)
This paper aims to examine the validity of the traditions relating to the events of the Prophet Muhammad prayer for Ibn Ubay. After doing the research it was found the conclusion that the histories related to the controversial event, all of them are Ṣaḥīḥ (authentic). Both the narrations which state that the Prophet prayed for Ibn Ubay, as well as narrations that